Philosophy in the context of physics and cosmology: Leszek M. Sokołowski’s philosophical views - Trombik, Kamil Piotr (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
The article attempts to reconstruct and analyze selected philosophical views of Leszek Sokołowski—a Krakow physicist and cosmologist who published many works dealing with issues on the border of science and philosophy (including metaphysics). An important aim of the article is also to place Sokołowski’s views in the context of the concept of “philosophy in science” (by M. Heller) and the phenomenon of the Kraków School of Philosophy in Science. In this paper, I suggest that Sokołowski’s views fit into the philosophy initiated by Michał Heller, and Sokołowski himself can be considered a member of the Kraków School of Philosophy in Science.